Pogledi na literarno zmožnost v didaktiki književnosti - Jožef-Beg, Jožica (Jezik in slovstvo, 2014)
The article deals with the specifics of the skills required to read literature as compared to general reading ability, providing a comparison of the role of literature in European school curricula, from which it is evident that teaching literature in Slovenian secondary schools is in line with European trends. By presenting some definitions and typologies of literary competence, the article draws attention to the different professional approaches in Slovenian and foreign literature, thus defining the position of literary competence development within the competence approach to teaching literature.
Keywords: didaktika književnosti; literarna zmožnost; srednje šole